1970
DOI: 10.3329/bjsir.v43i3.1156
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Akanda (<i>Calotropis gigantea</i> L.) on Some Pathogenic Bacteria.

Abstract: The antibacterial activity of methanol extract from the root bark of Akanda (Calotropis gigantea L.) and its petroleum ether, chloroform and ethyl acetate fractions were investigated. Both of methanol extract and its chloroform fraction showed activity against Sarcina lutea, Bacillus megaterium and Pseudomonas aeruginosa. Petroleum ether fraction showed activity against Bacillus subtilis and Shigella sonnei whereas ethyl acetate fraction showed activity against Pseudomonas aeruginosa and Escherichia coli at 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…[140] Similarly, C. procera latex and aerial plant parts showed antibacterial [141] and antifungal [142] activities against several pathogenic bacteria. [143,144] Insecticidal Activity C. procera latex and its chemical constituents showed larvicidal activity against third instar larvae of Anopheles stefensi, Culex quinquefasciatus, [145] Aedes aegypti [146] and Musca domestica, at a very low topical application of latex. [147] In addition, its sub-lethal dose also imposed significant effects on survival of larvae and pupae, inhibit growth, cause reduction in body weight of larvae, and obstruct molting in larval stadia of Spodoptera litura.…”
Section: Wound Healing and Hepatoprotectivementioning
confidence: 99%
“…[140] Similarly, C. procera latex and aerial plant parts showed antibacterial [141] and antifungal [142] activities against several pathogenic bacteria. [143,144] Insecticidal Activity C. procera latex and its chemical constituents showed larvicidal activity against third instar larvae of Anopheles stefensi, Culex quinquefasciatus, [145] Aedes aegypti [146] and Musca domestica, at a very low topical application of latex. [147] In addition, its sub-lethal dose also imposed significant effects on survival of larvae and pupae, inhibit growth, cause reduction in body weight of larvae, and obstruct molting in larval stadia of Spodoptera litura.…”
Section: Wound Healing and Hepatoprotectivementioning
confidence: 99%
“…Leaves/ seborrheic dermatitis Antibacterial activity (Abalaka et al, 2010) Calotropis gigantean(L.) W.T. Aiton Latex/ toothache,corns Antibacterial activity (Alam et al, 2008;Subramanian and Saratha, 2010) ; wound healing (Waya et al, 2009) Senna tora L. Whole plant/ fever Antibacterial activity (Roopashree et al, 2008); antibacterial activity (Chavan et al, 2011) Cayratia trifolia (L.) Domin Stem/ used as emmenagogue PGE2 inhibition (Siriwatanametanona, 2010)…”
Section: Kidney Stonementioning
confidence: 99%
“…Wound contaminants are likely to originate from three main sources, namely the environment, the surrounding skin, and endogenous sources involving mucous membranes (Duerden, 1994). A literature survey of Calotropis species revealed that the plant latex contains mainly cardenolides and triterpenes with antibacterial activity against both Gram-positive and Gram-negative bacteria (Alam et al, 2008). Furthermore, calotropin, a proteolytic enzyme, and flavonoids in the latex were reported to possess marked antiinflammatory and antioxidant properties, respectively (Atal and Sethi, 1962;Sen et al, 1992).…”
Section: Resultsmentioning
confidence: 99%